2021
DOI: 10.1007/s00198-021-06008-z
|View full text |Cite
|
Sign up to set email alerts
|

Influence of denosumab on bone mineral density in a severe case of pregnancy-associated osteoporosis

Abstract: Pregnancy and lactation-associated osteoporosis (PLO) with predominantly subsequent vertebral fracture is a rare but severe disease with an estimated incidence of 0.4 in 100,000. In the past, patients with PLO have been predominantly treated with oral and i.v. bisphosphonates to reduce subsequent fracture risk. Hereby, the use of bisphosphonates in premenopausal women is controversial, as bisphosphonates know to persist in bone for many years and can be exposed and circulate in maternal serum and subsequently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 18 publications
(21 reference statements)
0
9
0
Order By: Relevance
“…PLO was first described in 1955 by Nordin and Roper [ 15 ]. Its incidence is estimated to be 4–8 cases per 1,000,000 women [ 8 , 16 ], but the precise incidence is probably higher due to undiagnosed cases. Back pain caused by a vertebral fracture is one of the most common symptoms of PLO, and more than two-thirds of the vertebral fractures in cases of PLO occur in a first pregnancy [ 2 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…PLO was first described in 1955 by Nordin and Roper [ 15 ]. Its incidence is estimated to be 4–8 cases per 1,000,000 women [ 8 , 16 ], but the precise incidence is probably higher due to undiagnosed cases. Back pain caused by a vertebral fracture is one of the most common symptoms of PLO, and more than two-thirds of the vertebral fractures in cases of PLO occur in a first pregnancy [ 2 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mean half-life of 60 mg denosumab is 25.4 days, and its concentration declines over a period of 4–5 months. Stumpf et al (2021) reported the case of a patient with PLO treated with denosumab along with calcium and vitamin D supplementation, which led to increases in BMD at the lumbar spine, femoral neck, and total hip by 21.2%, 5.6%, and 8.0% at 12 months and by 32.0%, 13.0%, and 11.5% at 18 months, respectively [ 8 ]. Another patient with PLO was treated with weekly teriparatide (56.5 μg/week) for 6 weeks, followed by denosumab (60 mg) for 6 months, and at 12 months, she exhibited increases in BMD from baseline at the lumbar spine (L2–L4) and femoral neck by 16.5% and 3.9%, respectively [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 PLO is a rare disease that occurs more frequently in primiparous women over 30 years of age, with most cases occurring during the third trimester of pregnancy or in the early postpartum period. 1,3,4 Severe and prolonged back pain is the most frequent complaint and results from the presence of vertebral fractures. 1,4 The development of PLO can be explained by changes in calcium metabolism that occur in pregnancy.…”
Section: Discussionmentioning
confidence: 99%